Genetics of schizophrenia (Review) - Trifu, Simona Corina (Exp Ther Med, 2020)
A comprehensive review of the body of genetic studies on schizophrenia seems even more daunting than the battle a psychiatrist wages daily in the office with her archenemy of a thousand faces. The following article reunites some genetic, epigenetic and environmental factors of schizophrenia from revered and vast studies in a chronological and progressive fashion. Twin studies set the basics of heritability and a particular study by Davis and Phelps considers the widely ignored influence of prenatal environment in the development of schizophrenia. Mostly ignited by linkage studies, candidate gene studies explore further by fine-mapping the hypothesized variants [mostly in the forms single nucleotide polymorphisms (SNPs) and less but with greater impact copy number variations (CNVs)] associated with the disease. Genome-wide association studies (GWAS) increase considerably the sample sizes and thus the validity of the results, while the next-generation sequencing (NGS) attain the highest yet unreplicated level of validity results.